Classification of stillbirth by relative condition at death (Re Co De) at various trimesters of pregnancy: a rural tertiary teaching hospital based study - Rajagopal, V. Meera; Betha, Kalpana; G., Satya Priya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: New global health figures show India to have the highest rates of stillbirth in the world. While maternal and under 5 child mortality rates have halved, stillbirth remains a neglected global endemic. To reduce stillbirths, the prevalence, risk factors and causes must be known. The aim of the present study is to know the prevalence and classify stillbirths by ReCoDe classification system at different trimesters of pregnancy. Methods: This was a retrospective study done between January 2013 to March 2017 at MediCiti Institute of Medical Sciences, a rural tertiary teaching hospital, Telangana, India. A total of 112 cases of stillbirths were included. Data was obtained on demographic variables, risk factors such as preeclampsia, etc. Data regarding mode of delivery, fetal asphyxia, were recorded. Results: Stillbirth rate was 12.1/1000 births. Fifty four percent of the women were unbooked. Preterm stillbirths were a majority (67%). The intra-partum still birth rate was low (15.1%) contrary to what is seen in low middle-income countries. Gestational hypertension/Pre-eclampsia, abruptio placenta, fetal growth restriction and oligohydramnios were the leading causes of stillbirths. Conclusions: Pregnant women from rural background with low socio-economic status are prone for stillbirths. As stillbirths were more among unbooked cases, the study highlights the importance of counselling, creating awareness in the rural areas regarding the importance of regular antenatal checkups. Identifying risk factors like pre-eclampsia, anemia etc., at early weeks will enable us to initiate appropriate strategies to improve pregnancy outcome.